2013
DOI: 10.1308/003588413x13629960046958
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of internet images of glenoid labral injuries

Abstract: INTRODUCTIONThe internet is a convenient source of health information used widely by patients and doctors. Previous studies have found that the written information provided was often inaccurate. There is no literature regarding the accuracy of medical images on the internet. The aim of this study was to assess the accuracy of internet images of injuries to the glenoid labrum following shoulder dislocation. METHODS The Google and Bing search engines were used to find images of Bankart, Perthes and anterior labr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…A UK observational study (n = 253) investigated the accuracy of Internet images of injuries to the glenoid labrum (fibrocartilaginous rim around the margin of the shoulder socket) following shoulder separation from accident or injury. 135 Google and Bing search engines were used to find relevant images. Three reviewers were asked to assess the accuracy of image labeling.…”
Section: Teleradiology Evidencementioning
confidence: 99%
“…A UK observational study (n = 253) investigated the accuracy of Internet images of injuries to the glenoid labrum (fibrocartilaginous rim around the margin of the shoulder socket) following shoulder separation from accident or injury. 135 Google and Bing search engines were used to find relevant images. Three reviewers were asked to assess the accuracy of image labeling.…”
Section: Teleradiology Evidencementioning
confidence: 99%
“…Freeman et al reported image search accuracy of orthopedic surgery in shoulder injuries, finding a 4 to 30% image inaccuracy, which was substantially lower accuracy than our results. 14 These and other medical specialties share image- and pattern-based recognition as a core component of medical competency. Image accuracy in educational materials is essential.…”
Section: Discussionmentioning
confidence: 99%
“…Web sites may provide incorrect or incomplete information for medical professionals and patients. 5 6 7 8 9 10 11 12 13 14 GIS uses the proprietary PageRank algorithm to sort images into the order in which they appear on the results page. This sorting is not based on accuracy to the search terms but is rather algorithmically generated according to proprietary rulesets that prioritize images from Web sites that are linked by other prominent Web sites.…”
mentioning
confidence: 99%